Turning Straw into Gold: Constantin von Tischendorf's Jewish Manuscript Collections - Molière, Maximilian de ca. 20./21.Jhd. (Jewish studies quarterly, 2025)
This study outlines Constantin von Tischendorf's lesser-known activities as a collector of Rabbanite and Qaraite books. Tischendorf amassed these items on two of his journeys to the eastern Mediterranean. They relate to his overall scholarly activities in significant ways, since their sale to the Imperial Public Library in Saint Petersburg gave him an opportunity to enter into conversation with Russian officials, who went on to fund his third journey, from which he brought a part of Codex Sinaiticus to Russia. His attitude towards Jewish sources was largely utilitarian: he thought of them as tools to better interpret the New Testament.